Two dimensional trans-rectal ultrasonographic studies in early pregnant murrah buffaloes - SINGH, GYAN; CHANDOLIA, RAMESH KUMAR; DUTT, RAVI; DALAL, JASMER; SAINI, ANIL; MALIK, RAKESH KUMAR (The Indian Journal of Animal Sciences, 2018)
Two dimensional ultrasonographic studies were conducted in six pregnant Murrah buffaloes using 5.0-7.5 MHz frequency rectal probe twice a week from day 18 to 60 days followed by weekly interval up to 90 days postin semination. Two dimensional images of antenatal fetal organs particularly fetal stomach, eye, limbs, heart, umbilical cord, thorax, liver and placentomes were imaged and variat ions in size of placentome, stomach and crown rump length were measured. Fetal heart beat was measured from day 26 to 90 which decreased with advancement of gestation. From the present study it may be concluded that early pregnancy can be diagnosed ultrasonogra phicallythrough trans-rectal approach by day 26 post insemination.